KEBIJAKAN TIDAK DEMOKRATIS,, DAN PELUANG EKONOMI (Studi Komparatif Indonesia dengan Negara-Negara Maju) - Tampongangoy, Deysi Livi (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: The state republic Indonesia Poverty "and" injustice "is the reason most often cited for thedisappointment of the people against the democratic system. Not much different from the developed countriesand other developing In some countries, instead of a bright economic as promised by the leaders ofdemocracy the newly elected, but the people even watched the deteriorating economic conditions, the gapincreased income, and control of economic opportunities by elites. in other places, where the Gross DomesticProduct (GDP), the upper middle class to reap the greatest benefits, while poor remain poorKeywords: Policy, Economic Opportunities